PENERAPAN MODEL PEMBELAJARAN KOOPERATIF JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS - Heni Nuroniah (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2020)
This study aims to improve the learning outcomes of class VII-A students of MTs Negeri 4 Garut in the social studies subject matter on maps, atlases, and globes. This type of research is a classroom action research conducted in two cycles, each of which is carried out in 2 meetings. Each meeting consists of the planning, action, observation and reflection stages. The subjects in this study were all students of class VII-A MTs Negeri 4 Garut in the odd semester of the 2018-2019 school year, totaling 24 students. The data obtained in this study included: learning outcomes and student learning completeness which were taken from giving test questions at the end of each meeting and the activeness of students in the learning process. From the research data, it was found that the average learning outcomes of students in cycle I was 75 and cycle II was 86. The average completeness of learning in cycle I was 75% and cycle II was 100%. From these data it is clear that from cycle I to cycle II there is a significant increase. From this research, it is concluded that using the jigsaw cooperative learning model can improve the learning outcomes of students in class VII-A MTs Negeri 4 Garut on social studies subject matter maps, atlases, and globes.